Accessibility and exchange of plant germplasm by Embrapa - Bustamante,Patrícia Goulart (2011)
This paper presents information about the organizational structure of Embrapa's banks and collections of plant germplasm and lists the 14 projects that comprise the Plant Genetic Resources Network which houses about 200 000 access and correspond to a collection of 300 genera, 787 species (90 % exotic). The main goal of the Plant Genetic Resources Network is being a source of variability for breeders of nationally and internationally research institutions. The paper also presents the different ways of knowing and accessing the collection of plant genetic resources maintained at Embrapa. Special emphasis is given to the way of the researchers can import and export plant germplasm, including presentation of a series of accessions exchanged in the last 35 years by Embrapa Genetic Resources and Biotechnology. The paper also provides the necessary documents and specifies the step-by-step to exchange and quarantine of germplasm held by Embrapa Genetic Resources and Biotechnology.